2006
DOI: 10.1021/ic0615628
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Bis(thiosemicarbazonato) Complexes of Zinc and Copper:  Synthetic Platforms Toward Site-Specific Radiopharmaceuticals

Abstract: Two new types of unsymmetrical bis(thiosemicarbazone) proligands and their neutral zinc(II) and copper(II) complexes have been synthesized. These bifunctional ligands both chelate the metal ions and provide pendent amino groups that can be readily functionalized with biologically active molecules. Functionalization has been demonstrated by the synthesis of three water-soluble glucose conjugates of the new zinc(II) bis(thiosemicarbazonato) complexes, and their copper(II) analogues have been prepared in aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
112
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 64 publications
4
112
0
Order By: Relevance
“…2B) and demonstrated that copper-zinc exchange could be used to prepare the 64 Cu-radiolabeled compound 64 Cu-ATSE/ A-G (Fig. 2C) (19). In this article, we describe the oxygendependent uptake of 64 Cu-ATSE/A-G into HeLa cells in vitro and preliminary in vivo imaging results obtained in male BDIX rats with implanted P22 syngeneic carcinosarcomas.…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…2B) and demonstrated that copper-zinc exchange could be used to prepare the 64 Cu-radiolabeled compound 64 Cu-ATSE/ A-G (Fig. 2C) (19). In this article, we describe the oxygendependent uptake of 64 Cu-ATSE/A-G into HeLa cells in vitro and preliminary in vivo imaging results obtained in male BDIX rats with implanted P22 syngeneic carcinosarcomas.…”
mentioning
confidence: 83%
“…The proligand H 2 -ATSM, Zn-ATSM, and Zn-ATSE/A-G were prepared according to published methods (17)(18)(19)(20).…”
Section: Synthesis Of Labeling Precursorsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Complexes were prepared at a specific activity range of 1-1000 mCi/μg ligand. All complexes were prepared in sufficient radiochemical purity (>95%, determined by radio-TLC and identity confirmed by direct comparison with the elution profile of the authentic nonradioactive analog) to undertake in vitro and in vivo studies.…”
Section: Labeling Of 64 Cu Complexesmentioning
confidence: 99%